THE USE OF ARTIFICIAL INTELLIGENCE IN ANALYZING HISTORICAL DEMOGRAPHIC DATA - Fatma Amri; Rania Haddar (International Journal of Innovative Technologies in Social Science, 2025)
This paper aims to highlight the most significant artificial intelligence technologies and tools employed in processing historical demographic data, and explores the primary challenges that arise after their implementation. Advanced AI technologies have revolutionized the analysis of historical demographic data and the prediction of future trends, what enhances our understanding of the past and addresses gaps in historical records. Nevertheless, several challenges emerge, including the accuracy of historical events that involve demographic, social, cultural, and economic aspects of populations and the various phases they have experienced, such as data distortion, bias, and ethical issues. These challenges may undermine the credibility of information for current or future generations and lead to decisions and predictions with substantial implications for social, health, and economic policies.